Integrating Fungi in the Drinking Water Regulation and in Guidelines for Materials in Contact With Drinking Water. Is there Room for Change? - Novak Babič, Monika (2021)
Drinking water is essential for life. To ensure its safe use, up to date regulation is promoted by the World Health Organization, but ultimately established by individual countries and states federations. The European Union uses directives transposed to Member-states legislation. This regulation targets specific bacterial pathogens, but changes, like climate alterations, increasing human population and antimicrobial resistance bring along the necessity to adjust regulation to emerging threats. The authors herewith discuss the integration of fungi in drinking water regulation and in guidelines for materials in contact with drinking water. Core species should be established with possible indicators and specificities of water distribution to more susceptible users.